The Influence of Product Quality, Religiosity, And Word of Mouth on Purchase Decisions Through Brand Trust: A Study of Dea Bakery in Malang - Pangestu, Dimas; Pradiani, Theresia; Hanif, Rifki (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
In an increasingly competitive business environment, companies are required to retain customers and influence their purchasing decisions. This is especially relevant in the food and beverage industry, which faces intense market competition. For Dea Bakery, understanding the factors that influence consumer purchasing decisions is essential for formulating effective marketing strategies and fostering customer loyalty. This study aims to analyze the influence of product quality, religiosity, and word of mouth on purchase decisions, with brand trust serving as a mediating variable among Dea Bakery consumers in Malang City. The research employs a quantitative method using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach. The sampling technique used is purposive sampling, with criteria including respondents who have previously purchased Dea Bakery products. The final sample consists of 100 respondents, with data collected through the distribution of questionnaires. Data analysis includes validity and reliability testing, encompassing Measurement Model Evaluation (convergent validity, construct reliability using Composite Reliability [CR], and discriminant validity). The Structural Model Evaluation (Inner Model) involves R-Square (R²) testing, direct hypothesis testing (path coefficients and t-statistics), indirect hypothesis testing (mediation analysis), and significance testing via bootstrapping. The results indicate that: 1) Product quality, religiosity, and word of mouth each have a significant influence on brand trust; 2) Brand trust has a significant influence on purchase decisions; and 3) Product quality, religiosity, and word of mouth significantly influence purchase decisions through brand trust as a mediating variable.